Risk Factors for Under-Five Children Severe Acute Malnutrition (SAM) in Grobogan Regency - Nuryanto, Nuryanto; Sidhin, Syaharani; Fala, Etika Nurul; Nissa, Choirun; Candra, Aryu; Purwanti, Rachma; Fitranti, Deny Yudi; Rustanti, Ninik; Habibi, Nur Ahmad (JURNAL INFO KESEHATAN, 2024)
Severe Acute Malnutrition (SAM) is a major health risk for children under five. Various factors, such as poor food intake, infections, family size, healthcare participation, maternal nutrition knowledge, and parenting practices, contribute to SAM. However, no studies have specifically examined these factors in under-five children in Grobogan Regency. This study aims to analyze the risk factors associated with severe acute malnutrition among children under five years old in Grobogan Regency. The study employed a quantitative case-control design involving children aged 0-59 months in Grobogan Regency, with 11 children with Severe Acute Malnutrition (SAM) as the case group obtained through total sampling, and 11 well-nourished children as the control group selected via matching. Key variables examined included energy, protein, fat, and carbohydrate intake, as well as infectious diseases, family size, participation in posyandu, maternal nutrition knowledge, and parenting practices. Descriptive analysis outlined the subjects and variables, with bivariate analysis using the Chi-Square test at a 95% confidence level (α=0.05). The results study show that the statistical analysis indicated that inadequate energy intake was significantly associated with SAM (p=0.008, OR=26.667), suggesting that children under five with insufficient energy intake are 26.667 times more likely to experience severe acute malnutrition compared to those with adequate energy intake. In contrast, adequate intake of protein, fat, and carbohydrates, as well as factors such as infectious diseases, family size (p=0.080), participation in posyandu (p=1.000), maternal nutrition knowledge (p=0.476), and parenting practices (p=0.198), did not demonstrate significant associations with SAM among these children. The conclusion is adequate energy intake has been identified as a significant risk factor for SAM among under-five children in Grobogan Regency. Conversely, factors such as adequate intake of protein, fat, and carbohydrates, infectious diseases, family size, participation in posyandu, maternal nutrition knowledge, and parenting practices were not recognized as significant risk factors.